Ethics, evil, and fiction - McGinn, Colin, 1950- (Clarendon Press ; Oxford University Press, 1997)
Bringing together moral philosophy and literary analysis in a way that offers new insights for both, McGinn examines the relations between morality, art and beauty. He shows the value of literary texts as sources of moral illumination.